Societal Perceptions Towards Persons with Disabilities:A Historical Perspective (Journal of Asian Development Studies, 2024)
This study critically analyzes disability and communal attitudes towards it across differentsocieties throughout history. Existing literature has been extensively reviewed to understanddisability in a historical context. The study demonstrates that disability has existed throughouthuman history, with societal responses shaped by cultural values and the prevailing mode ofproduction. It reveals discrimination against persons with disabilities (PWDs) during the Greekand Roman periods, where disabled individuals were often deemed unfit for society. Theemergence of capitalism exacerbated the marginalization of disabled people, relegating them toinstitutions. In contemporary society, persons with disabilities continue to face ableism andviolations of their rights